MERANCANG SISTEM PENGOLAHAN ATK BERBASIS WEB PADA PT. ARTHAASIA FINANCE - Muhamad Zahruddin; Indri Handayani; Nini Santika (Universitas Raharja, 2018)
PT. Arthaasia Finance is a company engaged in the field of finance, and has problems in making data collection such as the manufacture of stationery demand and in making reports every month still using Microsoft Word and Microsoft Excel. The need for ATK management system is very necessary. Due to the vastness of the management system being run, so the need for management of ATK becomes very important. This system development method refers to the design used in the form of SDLC (Software Development Lift Cycle) in the form of waterfall. Based on the results of research at PT. Arthaasia Finance can be concluded that the Design of Office Stationery Applications At PT. Arthaasia Finance is designed with ease in the process of operation, making it easier for users to access information, facilitate employees in doing the job quickly and efficiently, and facilitate the General Affairs Department staff in viewing data ATK, request data and facilitate in making reports and to reduce errors in recording which is done manually